Gambaran Karakteristik Pasien Dengan Neuropati Diabetik Pada Diabetes Melitus Tipe 2 - Mawaddah, Mawaddah; Susmiati, Susmiati; Lenggogeni, Devia Putri (Universitas Fort De Kock Bukittinggi, 2022)
Background: Diabetic neuropathy is the most common microvascular complication of DM type 2 in diabetes mellitus patients, it is known that 50% of type 2 DM patients experience diabetic neuropathy. Symptoms that occur in diabetic neuropathy are paresthesia, hyperalgesia, burning, sharp pain, deduction of pain and temperature perception. If these symptoms are not prevented, the impact will increase the risk of complications such as injuries to the feet, ulcerations which can result in gangrenous wounds so that the after effects are at risk of amputation of the lower extremities. The aim of the study was to describe the incidence of diabetic neuropathy in patients with type 2 DM. Methods: This research was a descriptive research using purposive sampling technique with a total sample of 52 respondents. Results: The results showed that the most age of diabetic neuropathy patients was 46-55 years, there were 36 respondents (69.2%), the sex was mostly female, there were 46 respondents (88.5%), the duration of suffering from diabetes was 6-10 years, there were 38 respondents (73.1%), while the results of blood glucose levels at most <200 gr/dl there were 42 respondents (80.8%). Conclusion: In this study it was stated that diabetic neuropathy has characteristics, namely age> 46 years, often occurs in women, suffers from DM for ≥5 years and with glucose levels ≤200 mg/dl. It is expected that diabetic neuropathy patients can control blood glucose levels. Keywords: Diabetes mellitus, Diabetic neuropathy